2023
DOI: 10.3390/bs13070593
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Stress and Its Association with Intimate Partner Violence Perpetration and Victimization

Abstract: Intimate partner violence (IPV) is a pervasive issue, and during the COVID-19 pandemic, it has been speculated that the prevalence rates of IPV increased. This paper aims to understand how pandemic-specific distress was related to experiencing and perpetrating IPV. Using self-reported survey data from 371 individuals living in the United States, this study used multiple logistic regressions to examine how reports of distress related to working from home, working outside the home, isolation, stay-at-home orders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, these findings need further study in light of evidence from other investigators showing a complex association between COVID-19 related distress and conflict and both psychological and sexual IPV victimization. For example, one study showed that higher levels of COVID-19 distress related to family relationships and higher levels of conflict about COVID-19 correlated positively with psychological IPV victimization, whereas higher levels of distress associated with friendships were correlated with a reduced likelihood of this form of IPV, and further no association was found between any type of COVID-19 related distress or conflict and sexual IPV victimization [ 51 ]. The combination measure of all forms of IPV was positively associated with the duration of stay-at-home orders, indicating a net increase in risk of IPV during lockdowns.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings need further study in light of evidence from other investigators showing a complex association between COVID-19 related distress and conflict and both psychological and sexual IPV victimization. For example, one study showed that higher levels of COVID-19 distress related to family relationships and higher levels of conflict about COVID-19 correlated positively with psychological IPV victimization, whereas higher levels of distress associated with friendships were correlated with a reduced likelihood of this form of IPV, and further no association was found between any type of COVID-19 related distress or conflict and sexual IPV victimization [ 51 ]. The combination measure of all forms of IPV was positively associated with the duration of stay-at-home orders, indicating a net increase in risk of IPV during lockdowns.…”
Section: Discussionmentioning
confidence: 99%
“…Although a wave of publications appeared in the initial wake of the pandemic predicting a "shadow pandemic" (UN Women, 2020), based on preliminary and anecdotal evidence, as a wider perspective and evidence base has developed, the picture remains unclear (Miller et al, 2022). Many studies report increases in IPA, but those encompassing more data and accounting for more confounds suggest these increases are smaller than predicted (Piquero et al, 2021;Thiel et al, 2022;Uzoho et al, 2023) and vary significantly, with IPA increasing in some contexts (e.g., Evcili & Demirel, 2022;Hamadani et al, 2020;Keilholtz et al, 2023;Romito et al, 2022;Soeiro et al, 2023), remaining unchanged in some contexts (e.g., Chiaramonte et al, 2022;Miller et al, 2022;Tierolf et al, 2021), and even decreasing in some contexts (e.g., Capinha et al, 2022;Estlein et al, 2022;Gosangi et al, 2021;Jetelina et al, 2021;Plášilová et al, 2021). Some evidence suggests that incidents of IPA did not substantially increase, but the severity did (e.g., Estlein et al, 2022;Gosangi et al, 2021;Stripe, 2020;Thiel et al, 2022;Trafford, 2022), mainly among those with a prior history of IPA (e.g., Lausi et al, 2021;Plášilová et al, 2021;Thiel et al, 2022).…”
Section: (How) Did Ipa Change During the Pandemic Period?mentioning
confidence: 99%
“…Strains unquestionably increased during the pandemic period, but their relationship with changes in IPA is weak (Buttell et al, 2021; Cunha et al, 2023; Gresham et al, 2021; Halperin et al, 2023; Hammett et al, 2022; Piquero et al, 2021). This is likely due to the nature of these strains and variations in individual circumstances; while some couples experienced exacerbation of existing strains or new strains, some experienced a reduction in strains (Estlein et al, 2022; Keilholtz et al, 2023; Wyckoff et al, 2023).…”
Section: Explaining Changes In Ipamentioning
confidence: 99%
“…Specific marginalized communities, too, proved more vulnerable to these trends. Increases in IPV were more prominent among women (Bhuptani et al, 2023), among communities of color in general and among Black and Native individuals more specifically (Wood, Baumler, Hairston, Brashear, & Temple, 2023;Bhuptani et al, 2023), among people with low SES, people facing stressors related to unemployment, and people facing homelessness (Keilholtz et al, 2023;McNeil et al, 2023;Wood et al, 2023), as well as among women facing socioeconomic vulnerabilities in particular (Bhuptani et al, 2023), and among sexual and gender minorities (Bhuptani et al, 2023). These trends also manifested differently for different groups; for example, Wood et al (2023) found that Black participants reported higher levels of sexual abuse, reproductive coercion, and coercive control, while Bhuptani et al (2023) found that the stressors of increased levels of anxiety and increased substance use were associated with IPV in male couples.…”
Section: Negative Health Outcomes and Ipv Victimizationmentioning
confidence: 98%
“…2023;Bhuptani, Hunter, Goodwin, Millman, & Orchowski, 2023;McNeil, Hicks, Yalcinoz-Ucan, & Browne, 2023). In addition to the presence of new stressors related to COVID-19, studies also found increased presence of specific stressors and increased incidence of IPV, such as mental illness or mental health distress (Keilholtz et al 2023;McNeil et al, 2023) and substance use (Bhuptani et al, 2023). Specific marginalized communities, too, proved more vulnerable to these trends.…”
Section: Negative Health Outcomes and Ipv Victimizationmentioning
confidence: 99%